2014
DOI: 10.1021/jo500230q
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Deprotonative Lithiation of Azobenzenes: Reactions and Mechanisms

Abstract: Whereas standard strong bases (n-BuLi, s-BuLi/TMEDA, n-BuLi/t-BuOK, TMPMgCl·LiCl, and LDA) reduce the N═N bond of the parent azobenzene (Y = H), aromatic H→Li permutation occurs with LTMP when a suitable director of lithiation (Y = OMe, CONEt2, F) is present in the benzene residue of the azo compound. The method allows direct access to new substituted azobenzenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…We have indeed observed that, instead of the diazirine ring lithiation (followed by attempted deuteration), t -BuLi adds to the NN bond of 3-phenyldiazirine ( 3 ) even at −115 °C to form tert -butyl­diaziri­dine 4 in quantitative yield after quenching with MeOH- d 4 and aqueous workup (Scheme ). Similarly, LDA/ i Pr 2 ND does not accomplish the CN 2 ring H/D exchange with 3 , but it reduces the NN bond, affording diaziridine 5 in 64% yield . NOTE: All reactions reported here have been carried out by the addition of a diazirine to a solution of organolithium, and the product yields have been determined by 1 H NMR spectroscopy.…”
supporting
confidence: 64%
“…We have indeed observed that, instead of the diazirine ring lithiation (followed by attempted deuteration), t -BuLi adds to the NN bond of 3-phenyldiazirine ( 3 ) even at −115 °C to form tert -butyl­diaziri­dine 4 in quantitative yield after quenching with MeOH- d 4 and aqueous workup (Scheme ). Similarly, LDA/ i Pr 2 ND does not accomplish the CN 2 ring H/D exchange with 3 , but it reduces the NN bond, affording diaziridine 5 in 64% yield . NOTE: All reactions reported here have been carried out by the addition of a diazirine to a solution of organolithium, and the product yields have been determined by 1 H NMR spectroscopy.…”
supporting
confidence: 64%
“…The yield decreased if the temperature for the lithiated species was changed from −78 °C to −40 °C (Entries 1 and 2), which may be an indication of a reductive attack by the organolithium reagent on the azo group [18]. The transmetalation to copper at −78 °C provided largely the same yields (Entry 3), although at −40 °C, using the cuprate gave a very low yield of 7% (Entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…In general, ortho -azobenzenes can be accessed either by using C–H activation methods with late transition metals like nickel, palladium, platinum or ruthenium [16,17], by deprotonation with metal bases [18,19], or by direct halogen-lithium exchange [19,20]. The latter has been shown to proceed with high efficiency in the synthesis of several ortho -substituted organometallic azobenzenes (Scheme 1) [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, directed ortho -metalation (DoM) is a powerful method for the synthesis of ortho -functionalized arenes, which otherwise are significantly more challenging to prepare by classical routes such as electrophilic aromatic substitutions and hydrogen nucleophilic aromatic substitutions that typically present significant drawbacks concerning regioselectivity . Alternatively, D o M ensures very high regioselectivity for the ortho -functionalization of arenes bearing a suitable directed metalation group (DMG) . Although a wide variety of DMGs have been described, many of them possess some limitations mainly related to the additional steps required to install and further remove them.…”
mentioning
confidence: 99%